Bridging collaboration gaps in fragmented environmental governance systems. Issue 124 (October 2021) - Hamilton, Matthew; Fischer, Alexandra Paige; Jasny, Lorien
Highlights: "Collaboration gaps" among interdependent actors complicate environmental governance. Third-party actors tend to bridge gaps, but gaps were prevalent in the governance system. Actors without capacity to implement policy were more likely to bridge gaps. Actors who could more readily access the benefits of coordination also bridged gaps. Abstract: Recent research highlights the challenge of achieving environmental governance goals in the absence of collaboration among interdependent policy actors. This article explores factors contributing to the likelihood of "collaboration gaps" among actors who are interdependent because their jurisdictions overlap. Analysis of data on collaboration among organizations involved in wildfire risk governance in Oregon indicates that interdependent actors are more likely to collaborate. Despite this tendency, nearly 75 % of possible collaborations between interdependent actors were absent. In turn, these collaboration gaps tended to be brokered by third-party actors, especially those lacking the authority to manage land themselves and those for whom the benefits of brokerage may be more immediately apparent. Taken together, these findings shed light on actors' strategies for navigating fragmented governance systems and highlight opportunities to improve risk mitigation outcomes by enabling greater coordination among interdependent actors.